PENGARUH MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS DI KELAS V SEKOLAH DASAR NEGERI 12 KAYUAGUNG - Marcella; Jumroh; Noviati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine whether there is an influence of the Contextual Teaching And Learning (CTL) learning model on student learning outcomes in the Natural and Social Sciences (IPAS) subject of class V of SD Negeri 12 Kayu Agung, academic year 2024/2025. This study uses a quantitative method using a true experimental type of experiment. The type of sample used in this study is random sampling, namely classes VB and VC. The data collection technique is in the form of multiple choice questions. The results of the research and discussion can be concluded that there is an influence of the Contextual Teaching And Learning learning model on student learning outcomes in the IPAS subject in class V of SD Negeri 12 Kayu Agung.